A floriated makara with its neck stretched around the medallion - Temples of India Project Team (Jio Institute, 2024)
Tablet-like plaques are placed on the adhisthana (facing east). These plaques depict various types of flora and fauna as well as hybrid creatures like kinnara, vyala, and makara. The plaques are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The central artwork of the plaque is in the form of a circular medallion surrounded by a foliage motif. Seen here is a floriated makara with its neck stretched around the medallion and the rear part integrated with flowing creeper motifs. The rest of the plaque is decorated with ardha padma (half lotus) and kalpa lata (creeper) motifs.